Analisis dan Perancangan Sistem Informasi Penjadwalan Rapat pada Kantor DPRD Provinsi Sumatera Utara dengan Metode Waterfall - M Rizky Ramadhan; M Angga Septiawan (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
Meeting scheduling is a crucial aspect of time and resource management at the DPRD Office of North Sumatra Province. This article aims to analyze and design an efficient and effective meeting scheduling information system. Through a needs analysis approach, this research identifies various challenges faced in the current scheduling process, such as schedule conflicts and lack of transparency. By employing a web-based system design method, it is expected that the resulting system can facilitate coordination among members, enhance efficiency, and simplify information access. The outcomes of this research are anticipated to significantly contribute to improving organizational performance at the DPRD of North Sumatra Province.